Polar plot maps by parametric strain echocardiography allow accurate evaluation of non-viable transmural scar tissue in ischaemic heart disease. (4th August 2015) - Mele, Donato; Fiorencis, Andrea; Chiodi, Elisabetta; Gardini, Chiara; Benea, Giorgio; Ferrari, Roberto
Abstract: Aims: Assessment of left ventricular (LV) transmural scar tissue in clinical practice is still challenging because magnetic resonance imaging (MRI) and nuclear techniques have limited access and cannot be performed extensively. The aim of this study was to verify whether parametric two-dimensional speckle-tracking echocardiography (2D-STE) can more accurately localize and quantify LV transmural scar tissue in patients with healed myocardial infarct (MI) in comparison with MRI. Methods and results: Thirty-one consecutive patients (age 56 ± 32 years, 29 males) with MRI and echocardiography performed after at least 6 months from an acute MI were studied. Apical LV longitudinal strain images by 2D-STE and short-axis contrast images by MRI were analysed to generate parametric bull's eye maps showing the distribution of the LV transmural scar tissue, whose extension was measured by planimetry and expressed as a percentage of the total myocardial area. Twelve patients also had early 2D-STE and MRI examinations after the acute MI. 2D-STE accurately quantified the extent of transmural scar tissue vs. MRI ( r = 0.86; limits of agreement 10.0 and −9.5%). Concordance between 2D-STE and MRI for transmural scar tissue localization was high, with only 3.6% of discordant segments using an LV 16-segment model. Lin coefficients, intra-class correlation coefficients, and Bland–Altman analysis showed very good intra- and inter-observer reproducibility for 2D-STE evaluations. The transmural scar tissue area at 6 months could be predicted by early 2D-STE evaluation. Conclusion: 2D-STE polar plots of LV longitudinal strain characterize transmural scar tissue accurately compared with MRI and may facilitate its assessment in clinical practice.